Perhitungan Harga Pokok Produksi dalam Menentukan Harga Jual Tepung Mangga pada CV Wulan Jaya - Yudiastuti, Silvia Oktavia Nur; Dharmawan, Tedy; Perdana, Devtian Putera; Budiati, Titik; Wibisono, Yossi; Kusumasari, Findi Citra; Handayani, Wiwik; Ardhiarisca, Oryza (Jurnal Akuntansi Terapan dan Bisnis, 2024)
Mango is a tropical fruit that is rich in nutrients and has high economic value in Indonesia. Product innovation is important to increase selling value and reduce losses due to market competition. This study aims to calculate the Cost of Goods Produced of mango flour in determining the Selling Price per Kg at CV Wulan Jaya which is a mango producer company. The research method used is descriptive qualitative using quantitative data sourced from primary data. The cost of production of mango flour is Rp57,765 (rounded) plus a markup of 20% and an estimated marketing cost of 10% so that the selling price can be determined at Rp75,100 (rounded). This research emphasizes the importance of cost calculation in production planning and control to improve market competitiveness.